Heuristické metódy pre riešenie lokačnej úlohy s neohraničenými zdrojmi - Szendreyová, Alžběta; Matiaško, Karol (Univerzita Pardubice, 1998)
The design of a distributed database system involves making decisions on the placement of data and programs across the sites of a computer network. It is the main goal of our research work supporting by the faculty grant. In this paper we have suggested the basic mathematical model and some greedy algorithms for fundamental experiments on the modelled and real distributed database application. These experiments have been prepared with simulation support and we have prepared some heuristics models for next use.
Keywords: Database systems; heuristics models; locational problems